Intervista a Valerio Zunino della Studio SIT Srl - Renzo Carlucci (mediaGEO soc. coop., 2021)
Interview with Valerio Zunino, CEO of Studio Sit srl, a company operating in the geographic information field since more than 30 years. Recently experiencing a significant growth in the geolocation of streets numbers.